BUAH CEMARA INTEGRASI DAN INTERKONEKSITAS SAINS DAN ILMU AGAMA - Arsyad, Azhar (Institut Agama Islam Negeri (IAIN) Palu, 2011)
Abstract:Â Human beings possess three kinds of intruments to catch the whole reality. The three instruments are the five senses, reason and intellectuality as well as intuiion (revelation and inspiration)Â whreas the Western intellectluas agree one instrument only, namely the five senses so that theyÂ develope one research method only, namely observation method andÂ experiment. The observation method is continually developedÂ into very sopisticated level but it persistently derive fromÂ the sense perception. Reasonâin the form of reasoningâis employed, but only to choose, to decide and to perform reasoning, not asÂ other instruments to catch the reality. This makes the Western intellectuals different from the Muslim intellectuals since the laterÂ admit the validity of not only the observation methodÂ but also of the rational and intuitive method.Â Â Kata Kunci: integrasi, interkonektisitas, sains,Â ilmu agama, panca indera, akal